2019
DOI: 10.1096/fj.201900803r
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA SMAD5‐AS1 acts as a microRNA‐106a‐5p sponge to promote epithelial mesenchymal transition in nasopharyngeal carcinoma

Abstract: Nasopharyngeal carcinoma (NPC) is a malignant epithelial cancer of the head and neck with high prevalence in southern China, which is accompanied by notable invasiveness and metastasis. Long noncoding RNAs (lncRNAs) participate in the progression of various cancers including NPC. Microarray‐based analysis identified highly expressed lncRNA mothers against decapentaplegic homolog 5 (SMAD5)‐antisense RNA 1 (AS1) related to NPC. Interestingly, it is found that SMAD5‐AS1 competitively bound to microRNA (miR)‐106a‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 43 publications
1
36
0
Order By: Relevance
“…samples obtained from 68 patients. Functionally, differentially expressed lncRNAs are known as oncogenic factors in various human cancers 19,[33][34][35] In this study, we determined that LINC01106 exerted oncogenic role in CRC through promoting cell proliferation, mobility, EMT, and stemness. Our study is the first one to reveal the functions of LINC01106 in CRC progression.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…samples obtained from 68 patients. Functionally, differentially expressed lncRNAs are known as oncogenic factors in various human cancers 19,[33][34][35] In this study, we determined that LINC01106 exerted oncogenic role in CRC through promoting cell proliferation, mobility, EMT, and stemness. Our study is the first one to reveal the functions of LINC01106 in CRC progression.…”
Section: Discussionmentioning
confidence: 98%
“…Mechanistically, lncRNAs can regulate the expression of their downstream genes at transcriptional or posttranscriptional level. LncRNAs can act as positive regulators for mRNAs by acting as sponges for miRNAs [18][19][20][21] . In the current study, the possible downstream miRNAs of cytoplasmic LINC01106 were also detected.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, many studies have shown that one of the roles of lncRNAs is to regulate gene expression by competitively binding to miRNAs as competing endogenous RNAs (ceRNAs) in cancers. For instance, lncRNA linc00645 and SMAD5-AS1 have been reported as ceRNAs to mediate the progression of glioma and nasopharyngeal carcinoma by targeting miR-205-3p and miRNA-106a-5p, respectively (25,26). In the present study, we predicted miR-4722-3p as a potential downstream target of N13.3 by NONCODE database analysis.…”
Section: Discussionmentioning
confidence: 68%
“…More and more studies have shown that miRNAs play key roles in cancer chemotherapy resistance, and their potential role in determining drug sensitivity or drug resistance has been con rmed by several researches (14). As a member of the miR-17 family, miR-106a-5p is shown to be abnormally expressed in various tumors, including NPC (15), liver cancer (16) and colorectal cancer (17). Recently, overexpression of SOX4 has been found to be related to the occurrence, progression, invasion and metastasis in many various tumors, indicating that SOX4 may be a major determinant of NPC progression (18,19).…”
Section: Introductionmentioning
confidence: 96%